PENGARUH KEBUTUHAN PENGEMBANGAN DIRI (GROWTH NEED STRENGTH) DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA GURU SMP NEGERI KECAMATAN KARAWANG BARAT KABUPATEN KARAWANG - Anggie Andhini Pertiwi (Universitas Negeri Jakarta, 2014)
the objectives of this research was to investigate and to understand the effect of growth need strength and job characteristics on job satisfaction. It was a quantitative research which was conducted in six state junior high schools in West Karawang District located in Karawang Regency. The research used a survey method with path analysis applied in testing hyphotesis. The respondent sample are 151 teachers who are selected in a simple random way. The result of this research are: (1) There is a direct positive effect of growth need strength on job satisfaction. (2) There is a direct positive effect of job characteristics on job satisfaction. (3) There is a direct positive effect of growth need strength on job satisfaction.